Alternative to Water Based Fabric Cleaner in Textile and Detergent Processes. (31st January 2017) - Jain, Arpan
Abstract : Three different detergent formulations, (1) ethyl-hydro-oxides (EHOs, using ethanol + H2 O2 + KOH + water, without pH adjustment, at 60°C for 1 h), (2) modified EHOs (using ethanol + H2 O2 + KOH + water, with pH adjustment, at 40°C for 1 h), and (3) water based detergent (WBD, using commercial detergent T + water, at 40°C for 1 h), were analyzed for cleaning of dried biodiesel soaked cotton cloth (DBSCC) samples. The effects of detergent formulations were analyzed based on cloth sample weights (residual and intact) and visual (through photographic images) examinations. With EHOs formulations, the increasing concentration of KOH and H2 O2 had a significant effect on increasing both brightness and residual content of DBSCC samples. On the contrary, the controlled pH environments (as with modified EHOs formulations) had a significant effect in decreasing residual content and increasing brightness of DBSCC samples. The implications of EHOs formulations (with and without modification) are discussed with respect to current water based textile and detergent industries practices.